Strategic ballot removal: an unexplored form of electoral manipulation in hybrid regimes. Issue 4 (19th May 2019) - Friesen, Paul
ABSTRACT: The literatures on electoral manipulation and rejected ballots have yet to engage one another in a compelling manner. This article provides the theoretical foundations for rejected ballots as electoral manipulation by exploring incidents of suspicious rejected ballot rates and practices around the world with a special focus on Zambia. Not only did the rate of rejected ballots in Zambia double between the 2015 and 2016 presidential elections, but a disproportionate increase was observed in president's home province. Leveraging an original dataset, the article models a largely unnoticed form of electoral manipulation: the strategic rejection of opposition ballots by biased polling officials. Analysis reveals that more rejected ballots were associated with increased vote shares for the ruling party in the president's home province, indicating probable electoral manipulation. Raising awareness around this difficult to detect, but likely pervasive, form of manipulation should help to improve electoral quality in hybrid regimes.